Biologic therapy for amyloid A amyloidosis secondary to rheumatoid arthritis treated with interleukin 6 therapy: Case report and review of literature. Issue 32 (13th August 2021) - Jung, Ju-Yang; Kim, Young-Bae; Kim, Ji-won; Suh, Chang-Hee; Kim, Hyoun-Ah
Abstract: Introduction: Secondary amyloidosis is a rare complication of rheumatoid arthritis (RA) that is histologically characterized by the deposition of amyloid fibrils in target organs, such as the kidneys and gastrointestinal tract. Controlling the inflammatory response is essential to prevent organ dysfunction in amyloid A (AA) amyloidosis secondary to RA, and no clear treatment strategy exists. Patient Concerns and Diagnosis: A 66-year-old woman with RA, who had been treated with disease-modifying anti-rheumatic drugs for 1 year, presented with recurrent abdominal pain and prolonged diarrhea. Endoscopy showed chronic inflammation, and colon tissue histology confirmed AA amyloidosis. Interventions and Outcomes: After tocilizumab therapy was begun, her diarrhea and abdominal pain subsided, and articular symptoms improved. Biologic drugs for RA have been used in patients with secondary AA amyloidosis, including tumor necrosis factor and Janus kinase inhibitors, interleukin 6 blockers, and a T cell modulator. Here, we systematically review existing case reports and compare the outcomes of RA-related AA amyloidosis after treatment with various drugs. Conclusion: The data indicate that biologic drugs like tocilizumab might be treatments of choice for AA amyloidosis secondary to RA.